The Effects of Total Sleep Deprivation on Attention Capture Processes in Young and Older Adults: An ERP Study. Issue 2 (15th March 2023) - Tavakoli, Paniz; Murkar, Anthony; Porteous, Meggan; Carrier, Julie; Robillard, Rebecca
ABSTRACT: Background: The present study investigated whether sleep deprivation affects attention capture in young and older adults using event-related potentials (ERPs). Methods: Eleven young adults (20–30 y) and nine older adults (60–70 y) were tested following both normal sleep (NS) and total sleep deprivation (TSD). ERPs were recorded during an auditory discrimination task consisting of standard and deviant stimuli. Results: Deviant stimuli elicited the MMN, P3a, and RON ERPs. TSD attenuated the differences in reaction times between standards and deviants in young adults but not older adults. The P3a was attenuated in older adults compared to young adults. Older adults had a larger RON amplitude compared to young adults following NS, but not TSD. Conclusions: The reduced P3a and the absence of behavioral performance alteration in the older group suggests that older adults may utilize different neural processing strategies compared to younger adults to compensate for age-related declines in neural resources for attention capture. Sleep loss influenced age-related differences on the RON, suggesting that older adults may have reduced access to compensatory strategies following sleep loss.